Determinasi Harga, Kualitas, Dan Ketersediaan Produk Terhadap Loyalitas Pelanggan Tabung Gas LPG 3 Kg (Studi Kasus Pangkalan Silet Adi Putro Kota Malang) - Achasia, Prima Nur; Basalamah, Muhammad Ridwan; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine and analyze the effect of pricing, quality, and product availability on customer loyalty of 3 Kg LPG gas cylinders in Pangkalan Silet Adi Putro, Malang City. These factors are very crucial in determining whether customers will continue to use the product or switch to another provider. Therefore, understanding the relationship between price, quality, and product availability on customer loyalty is an important aspect in LPG gas business management. The research method used is a quantitative approach with a sampling technique using the purposive sampling method. Data were collected through a questionnaire using a Likert scale as a measuring tool distributed to 3 Kg LPG gas cylinder customers to determine their perceptions of price, quality, and product availability. The number of samples was determined using the Slovin formula with a total of 85 respondents. The data analysis test in this study used a validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis test, hypothesis test, and coefficient of determination test (Adjusted R²) using SPSS software version 25. The results showed that price, quality, and product availability factors simultaneously influenced customer loyalty. In addition, partially competitive prices, good product quality, and consistent availability have a significant effect on customer loyalty, indicating that improvements in each of these aspects can increase overall customer loyalty. Keywords : Price Determination, Quality, Product Availability, Customer Loyalty